Balancing control of neutral‐point voltage for three‐level T‐type inverter based on hybrid variable virtual space vector. Issue 4 (1st March 2020) - Zhou, Jiancheng; Cheng, Shanmei; Hu, Zhenyu; Liu, Jiang
Abstract : A three‐level T‐type inverter has higher efficiency and lower output voltage harmonics compared with the traditional two‐level inverter. However, neutral‐point voltage fluctuation and common‐mode voltage (CMV) can negatively affect the performance of the three‐level T‐type inverter. This study proposes a novel hybrid variable virtual space vector (HV 2 SV) strategy to mitigate this problem. Based on the virtual space vector scheme, new variable virtual small and medium vectors are reconstructed with the principle that the change of neutral‐point charge of each virtual vector in a switching period is zero, and the adjustment factor is further added to the virtual vector to achieve the balance of the neutral‐point voltage. At the same time, the vectors with a large CMV are eliminated to ensure that the CMV is minimised. Therefore, the HV 2 SV has excellent neutral‐point voltage balance control capability and common‐voltage suppression at both high‐ and low‐modulation ratios. Theoretical analysis, simulations, and experimental results demonstrate the effectiveness and feasibility of the proposed strategy for full modulation ratios.